Impulsividade e controle inibitório: avaliação cognitiva, comportamental e diagnóstica na demência frontotemporal - Luciano Inacio Mariano (2017)
The differential diagnosis between behavioural-variant Frontotemporal Dementia (bvFTD) and Alzheimer's disease (AD) represents a challenge in clinical neuropsychology. Typically, bvFTD patients exhibit behavioural disorders characterized by early and marked disinhibition. Hence, tests tapping into inhibitory function and impulsivity, like intertemporal choice, may be valuable for the differential diagnosis between bvFTD and AD. Our sample comprised three groups of participants: 25 mild AD patients (age 74.6 ± 9.7, 13 males), 27 mild bvFTD patients (age 67.8 ± 9.8, 14 males) diagnosed according to standard criteria - and 24 healthy controls (age 70.8 ± 8.3, 18 females). The groups were matched for sex, education and income. All participants underwent a neuropsychological battery, comprising 10 cognitive tests, focusing on inhibitory capacity and/or impulsivity (e.g.: Stroop, and Hayling test) and 2 behavioural measures (Starksteins Apathy Scale and Barratt Impulsivity Scale BIS-11). We also employed a Delay Discounting Task (DDT). There was no difference between AD and bvFTD in any of the neuropsychological measures of inhibitory control, such as Hayling Test (bvFTD 18.2±13.2, AD: 17.4±9.6, p=1.00) and the DDT (bvFTD 0.053±0.09, AD: 0.058±0.07, p=1.00). On the other hand, there was a difference between clinical groups regarding behavioural measures (BIS-11: bvFTD 76.1+9.5, AD 62.9+13.5, p=0.001; Apathy: bvFTD 28.1+7.8, AD 16.9+9). In the BIS-11, AD and controls performed similarly. ROC curve analysis for the differential diagnosis between AD and bvFTD demonstrated that BIS-11 and Apathy Scale had higher diagnostic accuracies than inhibitory/impulsivity neuropsychological tests: to BIS-11 a cutoff of 68 had 80% specificity and 68.2% sensitivity; and to Apathy Scale a cutoff of 23 achieved 77.8% specificity and 78.3% sensitivity, both between AD and bvFTD. Conclusions: Contrary to our expectations, neuropsychological tests of inhibitory control and impulsivity, such as Hayling and DDT were not useful for the differential diagnosis between these disorders. Nonetheless, BIS-11 did demonstrate diagnostic ability to distinguish bvFTD and AD, reinforcing that behavioural impulsivity is a hallmark of the former condition. The dissociation between cognitive and behavioural measures may be considered for the development of new cognitive tests for the early diagnosis of bvFTD